Effects of increasing maize planting density on yield, water productivity and irrigation water productivity in China: A comprehensive meta-analysis incorporating soil and climatic factors - Mingwei Zhou; Yongcui Wang; Jian Gu; Ningning Ma; Wenjie Hou; Jiaqi Sun; Xiaobing Fan; Guanghua Yin (Agricultural Water Management)
Increased planting density (IPD) has been widely implemented, yet its impact on maize yield, irrigation water productivity (IWP), and water productivity (WP) remains unclear. Utilizing data sourced from peer-reviewed publications, we conducted a meta-analysis to (1) examine the effects of varying planting densities on maize yield, (2) further investigate the influence of soil properties and the climate-whether dry or wet-on maize yield, IWP, and WP across increasing maize planting densities, and (3) assess the effects of fertilizer application on maize yield, IWP, and WP across increasing maize planting densities. The results showed that increasing planting density was effectively increased the total maize yield by about 13.3 %, IWP by about 16.7 % and WP by about 7.9 %. Soil type and wet/dry conditions also significantly affected maize, with the highest yield increase in silty (30.2 %) and dry semi humid (13.6 %), WP in (loamy: 18.7 %) and dry semi humid (15.7 %), and IWP in loamy (30.3 %) and semi arid (17.8 %). Therefore, in our study, we recommended the following for maize production practices in China: the best soil type for maize cultivation is recommended to be silty, the climate type is dry semi-arid; the recommended planting density is recommended to be 75,000–90,000 plants·ha−1, with irrigation ranging from 200 to 400 mm irrigation, 200–300 kg·ha−1 of nitrogen fertiliser, and 200 kg·ha−1 or more of phosphorus and potash fertiliser to maximise yield. This research highlights the strategic importance of tailored planting and irrigation practices for sustainable maize production and offers practical guidance for farmers and policymakers.